Ultrafast Vibrational Dynamics of Membrane‐Bound Peptides at the Lipid Bilayer/Water Interface. Issue 42 (18th September 2017) - Tan, Junjun; Zhang, Baixiong; Luo, Yi; Ye, Shuji
Abstract: Vibrational energy transfer (VET) of proteins at cell membrane plays critical roles in controlling the protein functionalities, but its detection is very challenging. By using a surface‐sensitive femtosecond time‐resolved sum‐frequency generation vibrational spectroscopy with infrared pump, the detection of the ultrafast VET in proteins at cell membrane has finally become possible. The vibrational relaxation time of the N−H groups is determined to be 1.70(±0.05) ps for the α‐helix located in the hydrophobic core of the lipid bilayer and 0.9(±0.05) ps for the membrane‐bound β‐sheet structure. The N−H groups with strong hydrogen bonding gain faster relaxation time. By pumping the amide A band and probing amide I band, the vibrational relaxation from N−H mode to C=O mode through two pathways (direct coupling and through intermediate states) is revealed. The ratio of the pathways depends on the NH⋅⋅⋅O=C hydrogen‐bonding strength. Strong hydrogen bonding favors the coupling through intermediate states. Abstract : The energy transfer within amide bonds along the backbone of membrane peptides has been studied. Femtosecond infrared‐pump sum‐frequency generation (SFG) vibrational spectroscopy was used to track the energy transfer from the N−H group to the C=O group within the peptide backbone.